DNA/protein binding, cytotoxicity and catecholase activity studies of a piperazinyl moiety ligand based nickel(II) complex. (5th September 2016) - Mistri, Soumen; Puschmann, Horst; Manna, Subal Chandra
Graphical abstract: The interactions of a Ni(II) compound with CT-DNA and serum albumins were studied using electronic absorption and fluorescence spectroscopic techniques. The compound has binding affinity to CT-DNA in the order of 6.06 × 10 5 M −1 and it interact with serum albumins with ground state association process. Abstract: The Ni(II) complex, [Ni(HL)(SCN)2 (H2 O)]·2(DMF) (1 ) [HL = 6-methoxy-2-[2-(1-piperazinyl)ethylimino]methylphenol], was synthesized and characterized by X-ray crystal structure analysis and spectroscopic methods. The crystal structure of complex1 reveals a distorted octahedral coordination geometry around the nickel centre which forms a supramolecular assembly through hydrogen bonds. The interaction of complex1 with the calf thymus DNA (CT-DNA) was investigated using electronic absorption and fluorescence spectroscopic methods. The results show that complex1 has binding affinity to CT-DNA in the order of 6.06 × 10 5 M −1 . The interactions of complex1 with bovine serum albumin (BSA) and human serum albumin (HSA) were also studied using electronic absorption and fluorescence spectroscopic techniques and the analysis show that interaction of complex1 with BSA/HSA occur mainly with ground state association process. The number of binding sites and binding constant were calculated using double logarithm regression equation. Anticancer activity of1 in human breast (MCF7) cancer cell lines reveals dose dependent suppression of cell viability with IC50 value 64 ± 3.7 μM. Catecholase activity of1 has been investigated in methanol medium using 3, 5-di- tert -butylcatechol (3, 5-DTBC) as model substrate and the result shows that1 is active for catalyzing aerobic oxidation of 3, 5-DTBC to 3, 5-di- tert -butylbenzoquinone (3, 5-DTBQ).